A sequence-based phylogenetic study using t-coffee alignments - Hasnul 'Izad, Nur Syamimi Diana (2017)
T-Coffee is a multiple sequence alignments package used to align sequence. T Coffee has two main features; first, it provides a simple and flexible ways of generating multiple sequence alignment using heterogeneous data sources . The data from these sources are provided to T-Coffee via a library of pairwise alignment. Second feature is the optimization method, which is used to find the multiple alignments that best fit the pairwise alignment. Sequence alignment plays an important role in producing an accurate phylogenetic tree. The best tool which capable of producing good alignment from sequence is needed to support the phylogenetic inference. The objectives of this study is mainly to build multiple sequence alignment using T-Coffee method, to build a phylogenetic tree using UPGMA method and to validate the reliability of the phylogenetic tree by comparing with the SCOP classification. The results showed that majority of the cluster resemble SCOP classification. It also showed that less difference in percentage identities for each protein pairs will give the best protein cluster.